P75NTR is highly expressed in vestibular schwannomas and promotes cell survival by activating nuclear transcription factor κB. Issue 10 (26th June 2014) - Ahmad, Iram; Yue, Wei Ying; Fernando, Augusta; Clark, J. Jason; Woodson, Erika A.; Hansen, Marlan R.
<x xml:space="preserve">Abstract</x> Vestibular schwannomas (VSs) arise from Schwann cells (SCs) and result from the loss of function of merlin, the protein product of the NF2 tumor suppressor gene. In contrast to non‐neoplastic SCs, VS cells survive long‐term in the absence of axons. We find that p75NTR is overexpressed in VSs compared with normal nerves, both at the transcript and protein level, similar to the response of non‐neoplastic SCs following axotomy. Despite elevated p75NTR expression, VS cells are resistant to apoptosis due to treatment with proNGF, a high affinity ligand for p75NTR. Furthermore, treatment with proNGF protects VS cells from apoptosis due to c‐Jun N‐terminal kinase (JNK) inhibition indicating that p75NTR promotes VS cell survival. Treatment of VS cells with proNGF activated NF‐κB while inhibition of JNK with SP600125 or siRNA‐mediated knockdown reduced NF‐κB activity. Significantly, proNGF also activated NF‐κB in cultures treated with JNK inhibitors. Thus, JNK activity appears to be required for basal levels of NF‐κB activity but not for proNGF‐induced NF‐κB activity. To confirm that the increase in NF‐κB activity contributes to the prosurvival effect of proNGF, we infected VS cultures with Ad.IκB.SerS32/36A virus, which inhibits NF‐κB activation. Compared with control virus, Ad.IκB.SerS32/36A significantly increased apoptosis including in VS cells treated with proNGF. Thus, in contrast to non‐neoplastic SCs, p75NTR signaling provides a prosurvival response in VS cells by activating NF‐κB independent of JNK. Such differences may contribute to the ability of VS cells to survive long‐term in the absence of axons. GLIA 2014;62:1699–1712